Monetary policies to counter the zero interest rate: an overview of research - Seppo Honkapohja (Bank of Finland, 2015)
​Many central banks have lowered their interest rates close to zero in response to the crisis since 2008. In standard monetary models the zero lower bound (ZLB) constraint implies the existence of a second steady state in addition to the inflation-targeting steady state. Large scale asset purchases (APP) have been used as a tool for easing of monetary policy in the ZLB regime. I provide a theoretical discussion of these issues using a stylized general equilibrium model in a global nonlinear setting. I also review briefly the empirical literature about effects of APP's.
URN:NBN:fi:bof-201508211365
Keywords: E63; E52; E58; 330